Dose-Response Relationship Between Neuromuscular Electrical Stimulation and Muscle Function in People With Rheumatoid Arthritis. Issue 9 (13th June 2019) - Almeida, Gustavo J; Khoja, Samannaaz S; Piva, Sara R
Abstract: Background: Neuromuscular electrical stimulation (NMES) is a viable intervention for improving impaired muscle function in individuals with rheumatoid arthritis (RA). However, there is limited evidence about the dose-response relationship between NMES and muscle function in these individuals. Objective: The objectives of this study were to investigate the dose-response relationship between NMES and muscle function in individuals with RA and to establish the minimal NMES training intensity for promoting improvements. Design: This study was a secondary analysis of data obtained before and after an NMES intervention in a randomized study. Methods: The study took place at a research clinic. Only adults diagnosed with RA were included. The intervention consisted of 36 NMES treatment sessions for the quadriceps muscles over 16 weeks. Muscle function was measured before and after the intervention; quadriceps cross-sectional area and muscle quality were assessed using computed tomography, and strength was measured with an isokinetic dynamometer. NMES training intensity was calculated as a percentage by dividing NMES-elicited quadriceps muscle torque by the maximum voluntary isometric contraction. Improvements in muscle function were calculated using paired-sample t tests. The dose-response relationship was determined using curve estimation regression statistics. The minimum NMES training intensity was defined as that sufficient to significantly improve all muscle function measures. Results: Twenty-four people (48 legs) participated (75% women; mean [SD] age = 58 [8] years; mean body mass index = 32 [7] kg/m 2 ). Quadriceps cross-sectional area, muscle quality, and strength improved after the intervention. Associations between NMES training intensity and muscle quality ( r 2 = 0.20) and strength ( r 2 = 0.23) were statistically significant, but that between NMES training intensity and muscle cross-sectional area was not ( r 2 = 0.02). The minimum NMES training intensity necessary to improve all measures of muscle function ranged from 11% to 20% of the maximum voluntary isometric contraction. Limitations: The relatively small sample size was a limitation. Conclusions: The minimum NMES training intensity for significant gains in muscle function was ∼15%. Higher NMES intensities may promote better muscle quality and strength in individuals with RA.